Establishment and characterization of a novel dedifferentiated chondrosarcoma cell line, NCC-dCS1-C1 - Oyama, Rieko; Kito, Fusako; Takahashi, Mami; Sakumoto, Marimu; Shiozawa, Kumiko; Qiao, Zhiwei; Noguchi, Rei; Kubo, Takashi; Toki, Shunichi; Nakatani, Fumihiko; Yoshida, Akihiko; Kawai, Akira; et al. (Human cell : official journal of Human Cell Research Society, 2019)
Dedifferentiated chondrosarcoma is an aggressive mesenchymal tumor of the bone, and novel therapies are needed to improve its clinical outcomes. Patient-derived cell lines are essential tools for elucidating disease mechanisms associated with poor prognosis and for developing therapies. However, few lines and xenografts have been previously reported in dedifferentiated chondrosarcoma. We established a novel patient-derived dedifferentiated chondrosarcoma cell line, NCC-dCS1-C1. Primary dedifferentiated chondrosarcoma tissues were obtained at the time of surgery and subjected to primary tissue culture. The cell line was established and authenticated by assessing DNA microsatellite short tandem repeats. The cells maintained in monolayer cultures exhibited constant growth, spheroid formation capacity, and invasion ability. When the cells were implanted into mice, they exhibited histological features similar to those of the original tumor. Genomic analysis of single nucleotide polymorphisms showed aberrant genomic contents. The DNA sequencing revealed the absence of IDH1 / 2 mutations. The global targeted sequencing revealed that the cell line preserved homozygous deletion of CDKN2A and CREBBP . A proteomic study by mass spectrometry unveiled similar but distinct molecular backgrounds in the original tumor and the established cell line, suggesting that tumor cell functions might be altered during the establishment of the cell line. Using a screening approach, four anti-cancer drugs with anti-proliferative effects at a low concentration were identified. In conclusion, a novel dedifferentiated chondrosarcoma cell line, NCC-dCS1-C1, was successfully established from primary tumor tissues. The NCC-dCS1-C1 cell line will be a useful tool for investigations of the mechanisms underlying dedifferentiated chondrosarcomas.